Menghadapi Stres Akademik: Solusi dari Perspektif Teologi Kristen untuk Mahasiswa - Intan Meida Sari Gea; Korina Sanosa; Ridwan Bangun; Amoli Ndraha (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2024)
The academic world is an important focus in doing assignments, which is a process that is full of obstacles because there are many challenges that students must go through while working on it. In Indonesia, there has been a threat to the well-being of students in the form of academic stress and there are various cases of the consequences of this pressure. This article aims to outline the importance of overcoming student stress in the academic field, as well as efforts to overcome the problem based on a biblical perspective on stress. Qualitative method with analytic descriptive approach, which explains the situation under study in detail through descriptive presentation. Qualitative research methods through literature studies related to "Theological Review of Academic Stress" can be accessed by reviewing journal articles and studying theories from the literature that support this research. This research can produce relevant data through analyzing various sources of information found by the researcher through explanations based on the researcher's observations of existing data. In the next stage, the research will explore the biblical or theological perspective on stress, relating it to academic stress. The research shows the results of the complexity of academic stress with implications for mental, emotional, and physical well-being as well as the quality of academic achievement. The theological perspective highlights how important it is to manage everyone's worries and stress based on a correct understanding of theology.